2006
DOI: 10.2165/00019053-200624080-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Adding Ezetimibe to Atorvastatin Therapy in Patients Not at Cholesterol Treatment Goal in Canada

Abstract: Our analysis suggests that adding ezetimibe to atorvastatin for patients not achieving treatment goals with their current atorvastatin dose produces greater clinical benefits than treatment with a fixed-dose atorvastatin or atorvastatin titration at an increased overall cost. The cost-effectiveness ratios provide strong evidence for the adoption of ezetimibe within the Canadian healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 54 publications
4
45
0
Order By: Relevance
“…Applying treatment effects and costs obtained from the VIDAL Dictionary (2005) (18) resulted in an ICER of €39,937 for ezetimibe added to statin monotherapy compared with statin alone. Thus, in the second‐line setting, the ICER for PR nicotinic acid as add‐on therapy in dyslipidaemic patients with CHD and persistently low HDL‐C levels compares favourably with that of ezetimibe add‐on therapy in patients with persistently elevated LDL‐C levels, which is consistent with previously reported data in other European countries and North America (29,30).…”
Section: Discussionsupporting
confidence: 88%
“…Applying treatment effects and costs obtained from the VIDAL Dictionary (2005) (18) resulted in an ICER of €39,937 for ezetimibe added to statin monotherapy compared with statin alone. Thus, in the second‐line setting, the ICER for PR nicotinic acid as add‐on therapy in dyslipidaemic patients with CHD and persistently low HDL‐C levels compares favourably with that of ezetimibe add‐on therapy in patients with persistently elevated LDL‐C levels, which is consistent with previously reported data in other European countries and North America (29,30).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, E/S was cost-effective at £30,000/QALY and the ICERs were below the £20,000/ QALY compared with branded atorvastatin [20]. The current evaluation assumed that E/S-related LDL-C decreases reduce CVD risk consistent with published evidence [7,[18][19][20]. The present analysis and other published data demonstrate that E/S has a greater probability for achieving goal LDL-C levels compared with statin monotherapy and decreases the risk of CVD events [7,16].…”
Section: Discussionsupporting
confidence: 57%
“…The impact of any treatment modification within the model is reflected in a probabilistic change in the patient's lipid profile with consequently altered CVD risk and health state over time [4,18]. Accordingly, the present model assumed that ezetimibe-associated lipid level decreases are associated with a CVD risk reduction.…”
Section: Model Structurementioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that adding ezetimibe to a statin was cost-effective (vs. statin monotherapy) [67]. In this study, the cost-effectiveness of treating patients with Eze/statins (vs. statin monotherapy with doubling of the statin dose) improved as a function of increasing CHD risk [67], given that ICER values decreased with increasing statin dose potency, which is in turn commonly construed as a surrogate for increased cardiovascular risk. On the other hand, a recent study in the United Kingdom using a Markov model projected that, in a hypothetical population of 1000 men aged 55 years with cardiovascular disease, adding Eze to a statin conferred 134 additional QALYs and averted 43 nonfatal MIs, 7 nonfatal strokes, and 26 cardiovascular deaths over the population's total lifespan, compared with doubling the statin dose; these data were consistent with an ICER value of £27,475/QALY compared with statin monotherapy up-titrated by 1 dose [68].…”
Section: Discussionmentioning
confidence: 79%